2010
DOI: 10.1364/oe.18.009780
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic resonances in optomagnetic metamaterials based on double dot arrays

Abstract: We study optical properties of optomagnetic metamaterials produced by regular arrays of double gold dots (nanopillars). Using combined data of spectroscopic ellipsometry, transmission and reflection measurements, we identify localized plasmon resonances of a nanopillar pair and measure their dependences on dot sizes. We formulate the necessary condition at which an effective field theory can be applied to describe optical properties of a composite medium and employ interferometry to measure phase shifts for ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…the basis has two metallic nanoparticles rather than the more usual one-particle basis. Dimer arrays have been investigated before, but predominantly for out-of-plane dipole moments [19,27,28], here our focus is on in-plane dipole moments. Whilst out-of-plane SLRs can be supported by arrays of plasmonic nanoparticles in an asymmetric environment (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…the basis has two metallic nanoparticles rather than the more usual one-particle basis. Dimer arrays have been investigated before, but predominantly for out-of-plane dipole moments [19,27,28], here our focus is on in-plane dipole moments. Whilst out-of-plane SLRs can be supported by arrays of plasmonic nanoparticles in an asymmetric environment (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Kravets et al recently indicated that ''holes in the fishnet structures are not actually necessary to produce negative index of refraction using MSM''. 62) Therefore, the negative refraction as observed in this work will not be attributed to magnetic phenomena at optical frequencies. …”
Section: The Goos-hänchen and Optical Magnetism Effectsmentioning
confidence: 62%
“…Array dimensions were confirmed using scanning electron microscopy (SEM). Sample fabrication was discussed in depth in previous works 30, 56, 57 .…”
Section: Methodsmentioning
confidence: 99%